Civil Society and Global Governance: The Indirect Participation of Extinction Rebellion in Global Governance on Climate Change - Wahyu Rozzaqi Ginanjar; Ahmad Zakky Mubarrok (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2020)
The climate change problem is one of the global challenges faced by global society today. These problems certainly need to be adress in serious manners, especially at the global level. However, for some people, especially at the grassroots, consider global governance related to climate change today is not serious enough to deal with these problems. That is because the nature of the global climate regime is somehow voluntary and non-binding. In this case, civil society can provide the opportunities for the people to contribute to global governance related to climate change. Civil society here can be interpreted as a political space, where association of people can work towards the formation of social and legal rules through non-formal political channels. Extinction Rebellion is one of the civil societies that involves themselves in global discourse related to climate change in international politics arena. This article discusses the form of Extinction Rebellion's involvement in the global climate regime and what dimensions could potentially affected by the movement. This article uses descriptive-qualitative methods with library research data collection techniques. This article found that Extinction Rebellion’s involvement in global governance is an indirect involvement with resistance as their mode of participation, which is indicated by the emergence of mass protest in various cities around the world. In addition, Extinction Rebellion initiate discourse on climate change emergencies to illustrate how important climate problems must be handled seriously at the global level.